Produktivitas Jamur Merang (Volvariella Volvaceae)Pada Media Campuran Tongkol Jagung Dan Jerami PadiDengan Cara Penanaman Yang Berbeda - Pratiwi, Alfiani Indah, Dra. Suparti, M.Si (2017)
Corncob is a very abundant lignocellulosic waste of its existence, so corncob can be used as media for planting mushroom. The purpose of this research is to know the productivity of mushroom on mixture media of corn cob and rice straw that is planted in baglog and basket. This study used experimental method with complete randomized design (RAL) with 2 factors and 3 repetitions. Factor 1 by weight of corn cob: (T1) 125g, (T2) 250g, (T3) 375g, (T4) 500g. Factor 2 ways of planting: (K) basket, (B) baglog. Parameters measured were the number of fruit body and body weight of mushroom fruit. Data were tested with 2 lane anava analysis. Based on the analysis of variance shows that the addition of different corn cobs by way of planting in baglog and basket gives effect to the number of fruit body and body weight of mushroom fruit. The best treatment of mushroom is KT2 treatment (250g mixture of corn cob, 250g planting straw in basket) that is the average number of fruit body 12.3 fruit and fruit body weight 205,5g, while the number of mushroom fruit body merang lowest in treatment BT4 (500g corncobs, no straw, planting in baglog) the number of fruit body averages 2.2 pieces and fruit body weight 37.7 g.